Proceedings of the 20th SIRWEC conference, Druskininkai, Lithuania (14-16th June 2022) - Šidlauskaitė , Lauryna; Kažys , Justas; Kaminskas, Jonas (Vilnius University Proceedings, 2022)
SIRWEC (The Standing International Road Weather Commission) exists to encourage meteorologists, weather forecasters, highway engineers, road masters and others, who are interested in road weather problems, to exchange ideas to make our roads safer to drive on in all weather conditions.Every two years SIRWEC conference is being organized to gather all of the road weather enthusiasts and encourage them to share new scientific discoveries they have accomplished, new products or technologies they have made or any other topic in road weather field.
Keywords: Road meteorology; SIRWEC; Winter Road Maintenance; RWIS; road weather